Die self-sny fenomeen onder jongmense: perspektiewe vanuit die praktiese teologie - W. Coetzer (Acta Theologica)
Statistics around the phenomenon of self-injurious behaviour show a rise in numbers. Self-injury has been described as the anorexia and bulimia of the new millennium. The church must be equipped to guide and counsel young people affected by this problem. It is not a ‘teenage problem’ that people simply ‘outgrow’. We can therefore no longer pretend that this is a fringe issue that occurs in only the most extreme cases. This article, in the first instance, focuses on reasons for the increase in cases as well as on a number of misconceptions regarding this theme. Secondly, the focus shifts to the important role of emotions, the dynamics of the process, as well as a treatment programme. In conclusion, a number of pastoral perspectives are highlighted and guidelines provided to prevent possible slips and setbacks.